Tissue Culture Propagation of Afzelia africana Sm. Ex. Pers. – A Potential Candidate for Biofuel - OGBIMI, Ejeoghene; OMISOPE, Babajide; SAKPERE, Ayobola; AFOLAYAN, Adedotun (Journal of Tropical Biology & Conservation (JTBC), 2024)
This study, the first of its kind reports an in vitro shoot regeneration protocol in Afzelia africana. A. africana is a medicinal and multipurpose tree that is under permanent pressure from its continuous exploitation for medicine, food and timber products. Adding to its being under threat of extinction, the seeds are dormant and recalcitrant with a low rate of seed germination thus posing a challenge on its propagation through conventional planting. In vitro propagation method is appropriate for propagating A. africana since it can boycott the use of seeds. Leaf, nodal, cotyledonary node, shoot tip, stem and hypocotyl explants were cultured on Murashige and Skoog (MS) medium 1962 diluted with different concentrations and combinations of plant growth regulators and phloroglucinol. Two sets of experiment were done; the first was a preliminary one that tested the responsiveness of explants in vitro while the second tested the effect of thiaduzuron, benzyladenine and phloroglucinol on shoot multiplication and elongation from cotyledonary node explants. Although, both the cotyledonary node and nodal explants induced multiple shoots, the response was better in cotyledonary explants, hence the shoot multiplication protocol was maximized using cotyledonary nodes. This study has paved a path for the rapid regeneration of A. africana through in vitro propagation.